Fluidity of mica particle dispersed aluminium alloy - Deonath; Rohatgi P.K. (My University, 2025)
Cast aluminium alloy-mica particle composites were made by dispersing mica particles in a vortex produced by stirring the liquid Al-4 wt% Cu-1.5 wt% Mg alloy and then casting the melt containing the suspended particles into permanent moulds. Spiral fluidity and casting fluidity of the alloy containing mica particles in suspension were determined. Both the spiral fluidity and the casting fluidity of the base alloy were found to decrease with an increase in volume or weight percent of mica particles (of a given size), and with a decrease in particle size (for a given amount of particles). The fluidities of Al-4 wt% Cu-1.5 wt% Mg alloys containing suspended mica particles were found to correlate very well with the surface area of suspended mica particles. The regression equation for spiral fluidity Y (cm) as a function of surface area of mica particles per gram of spiral X (cm2 g-1) at 700° C was found to be Y=42.62-0.42 X with a correlation coefficient of 0.9634. The regression equations for casting fluidity Y′ (cm) as a functiono of surface area of mica particles per gram of fluidity test piece X′ (cm2 g-1) at 710 and 670° C were found to be Y′=19.71-0.17 X′ and Y′=13.52-0.105 X′ with correlation coefficients of 0.9194 and 0.9612 respectively. The percentage decrease in casting fluidity of composite melts containing up to 2.5 wt% mica with a drop in temperature is quite similar to the corresponding decrease in the casting fluidity of base alloy melts (without mica). The change in fluidity due to mica dispersions has been discussed in terms of changes in viscosity of the composite melts. However, the fluidities of these composite alloys containing up to 2.5 wt% mica are adequate for making a variety of simple castings including bearings for which these alloys have been developed. © 1980 Chapman and Hall Ltd.